Implementasi Kebijakan Konvergensi Pencegahan Stunting melalui Rumah Desa Sehat (RDS) di Desa Sindangsari Kecamatan Pabuaran Kab.Serang - Yeni Widyastuti; Arenawati Arenawati; Nikki Prafitri (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2022)
Regulation of Kemendes PDTT No. 16/2018 concerning Allocation of Village Funds (Alokasi Dana Desa/ADD) declare that one of the Village Funds priorities is to improve health services in village. The Healthy Village House (RDS) is a community centre whose role is to encourage health literacy in the village as well as to advocate for development policies in the village to be more focused on efforts to improve the health status of the community in the village. The establishment and development of RDS is facilitated by Kemendes PDTT as an effort to prevent stunting. The prevalence of stunting under five in Indonesia in 2019 reached 27.7 percent, still far from WHO target of 20 percent, and in Banten Province itself it reached 24.1 percent (Source: Study of Nutritious Toddler of the Ministry of Health, 2019). Stunting ins chronic nutritional problem who are characterized by a shorter height than the average age of children, children become susceptible to disease and when they are adults are at risk of degenerative disease. The stunting reduction acceleration program is one of the government’s priority program in the health sector and targeted 14 percent in 2024. The Healthy Village House (RDS) is a joint secretariat in the village, functioning as a transmitter of health information, that a person, family or community is able to help themselves (independently) in the health sector and play an active role in health development in the village, in this case including the stunting prevention convergence policy. Convergence policy is interpreted as an intervention approach carried out in a coordinated, integrated and jointly targeted manner in geographic areas and priority households to prevent stunting. Stunting prevention policies is a challenge during COVID-19 pandemic due to rising unemployment and poverty rate. Sindangsari Village has established the Healthy Village House (RDS) using allocation of village funds (ADD) and providing nutritional food assistance for stunting toddlers. This study aims to analyze the implementation of the stunting prevention convergence policy at the village level through the Healthy Village House (RDS) in Sindangsari Village, Pabuaran District of Serang Regency. Keywords: Convergence, Healthy Village House, Policy, Stunting